Simultaneous Determination of Content and Antioxidant Activity of Five Components in Hibiscus mutabilis L by HPLC-QAMS - Yang Xu; Xianwen Yue; Yuejie Wang; Huailei Yang; Kexin Di; Huiwei Bao (Journal of Chemistry)
Based on high performance liquid chromatography (HPLC), a method for simultaneous determination of five active components in Hibiscus mutabilis L was established by quantitative analysis of multicomponents by single marker (QAMS). This method was used to evaluate the quality of Hibiscus mutabilis L. In the study, quercetin was used as the internal standard, and the relative correction factors (RCF) of rutin, protocatechuic acid, catechin, and luteolin were calculated, and the contents of five components were determined simultaneously by quercetin. Compared with the traditional external standard method (ESM), this method had less error and higher feasibility, and the methodological experiments showed that the five components had a great linear relationship within their respective concentration ranges (r≥0.9995). The average recovery was 96.97%-98.85% (RSD was 0.88%-1.81%), precision (RSD≦1.83%), repeatability (RSD≦1.87%), and stability (RSD≦1.51%) were great. In this experiment, the contents of these five active components in Hibiscus mutabilis L from five producing areas were determined. Finally, the antioxidant capacity of Hibiscus mutabilis L was determined to determine its antioxidant activity.